First report of isolation and molecular characterization of bubaline herpesvirus 1 (BuHV1) from Argentinean water buffaloes - Maidana, Silvina Soledad; Konrad, Jose Luis; Craig, María Isabel; Zabal, Osvaldo Alfredo; Mauroy, Axel; Thiry, Etienne; Crudeli, Gustavo Angel; Romera, Sonia Alejandra (2018)
Herpesviruses have mainly co-evolved with their hosts for millions of years. However, bovine herpesvirus 1 (BoHV1) and related ruminant alphaherpesviruses have been reported to cross the species barrier. Bubaline herpesvirus 1 (BuHV1) is an alphaherpesvirus closely related to BoHV1 and BoHV5. According to the serological cross-relationships between ruminant alphaherpesviruses, several surveys have studied the occurrence of BoHV1-related virus infection in wild and domestic ruminant species. Recent studies in Argentina showed an increase in serological prevalence against BoHV1 related viruses in water buffaloes (Bubalus bubalis) population. The aim of this study was to investigate the presence of related ruminant alphaherpesvirus in the Argentinean water buffalo population. BuHV1 was successfully isolated from 5 out of 225 buffaloes analyzed. One isolate was obtained from nasal secretions, and the others were from vaginal swabs. The buffaloes belonged to four different farms located in northeastern Argentina. The isolates were characterized as alphaherpesvirus by direct immunofluorescence using FITC-anti-BoHV1 IgG. Restriction analysis performed with BamHI and BstEII on the complete genome showed differences between the isolates and those from BoHV1 and BoHV5 subtypes. Phylogenetic analysis on both UL27 and US6 showed similarity in tree topology. While three of the isolates grouped together with sequences of BoHV5, two other isolates clustered separately. Genetic analysis of eight concatenated sequences from all isolates and references strains showed high nucleotide sequence identity between BuHV1 and BoHV5. While three of the isolates clustered together with the BoHV5 reference strain, the last two isolates were closely related to an Australian BuHV1 strain. To our knowledge, this is the first report on the isolation and molecular characterization of BuHV1 in South America. Phylogenetic analysis suggested that two different BuHV1 lineages circulate in the Argentinean water buffalo population.